Surveillance Of Hospital Acquired Infection in Surgical Wards in Tertiary Care Centre Ahmedabad, Gujarat - Patel , Disha A; Patel , Kiran B; Bhatt , Seema K; Shah , Hetal S (National Journal of Community Medicine, 2011)
Present study was undertaken to know the rate of Hospital acquired infection in general surgical wards with special reference to surgical site infections with their antibiotic resistance pattern and to find out the source of the infection to develop preventive measures to reduce the risk of hospital acquired infection. Prospective surveillance for hospital acquired infections was performed during period from January 2006 to June 2006 in the wards of general surgery. One day prevalence study was carried out to find out rate of various hospital acquired infections. Incidence rate for Surgical Site Infection (SSI) found out by monitoring all operated cases throughout their stay, and after discharge. All surgical operation theatres were studied in detail to find out various physical parameters, policies and procedures, various cleaning procedures and fumigation. Over all prevalence rate of hospital acquired infections in surgical wards was about 21.9% comprising of 10.9% for SSI, 8% for local blood stream infection (i.e. thrombophlebitis) 2% for urinary tract infection (UTI) and 1% for the other infection (like bed sore). Incidence rate of surgical site infections was 12.72 %. Klebsiella spp. was the most common isolate responsible for SSI. The prevalence of HAI and incidence of SSI in our hospital has encouraged the development of recommendations for prevention of such infections in our hospital.